Consecutive shock waves and fatigue loads: action invariants as optimization parameters under Laser Shock Pinning (Fracture and Structural Integrity, 2025)
The criteria for optimizing shock-wave modes to increase the fatigue life of aircraft engine alloys are discussed with reference to laser shock peening (LSP). They are based on the self-similarity of plastic wave fronts and the kinetics of fatigue cracks related to the Swegle-Grady power law of structured plastic wave fronts and the Paris power law of fatigue crack advance. It is shown that the self-similar patterns and the power-law relationships of structured wave fronts at shock pulse amplitudes of 1-10 GPa and strain rates of 105-109 s-1 correspond to “action invariants” that determine the dissipative properties (stored energy) of materials caused by multiscale defect development. The relationship between the “action invariants” of structured plastic waves, the fatigue crack kinetics and the structural scaling invariants is shown using the 3D data of qualitative fracture surface profilometry. The methodological principles for studying material behavior under successive shock-wave and fatigue loads have been developed to optimize LSP processes and thus to ensure maximum fatigue life.
Keywords: Multiscale damage kinetics; VHCF; defect induced criticality; LSP; wave fronts; fatigue crack kinetics; action invariants; self-similarity; intermediate asymptotic; VISAR interferometry; fracture surface; quantitative fractography